Prognostic performance of the REDS score, SOFA score, NEWS2 score, and the red-flag, NICE high-risk, and SIRS criteria to predict survival at 180 days, in emergency department patients admitted with suspected sepsis – An observational cohort study - Sivayoham, Narani; Hussain, Adil N.; Sheerin, Thomas; Dwivedi, Prerak; Curpanen, Danalakshmee; Rhodes, Andrew (Frontiers in Medicine, 2023)
Background: Patients admitted to hospital with sepsis are at persistent risk of poor outcome after discharge. Many tools are available to risk-stratify sepsis patients for in-hospital mortality. This study aimed to identify the best risk-stratification tool to prognosticate outcome 180 days after admission via the emergency department (ED) with suspected sepsis. Methods: A retrospective observational cohort study was performed of adult ED patients who were admitted after receiving intravenous antibiotics for the treatment of a suspected sepsis, between 1st March and 31st August 2019. The Risk-stratification of ED suspected Sepsis (REDS) score, SOFA score, Red-flag sepsis criteria met, NICE high-risk criteria met, the NEWS2 score and the SIRS criteria, were calculated for each patient. Outcome (all-cause mortality) at 180days was noted. Patients were stratified in to high and low-risk groups as per accepted criteria for each risk-stratification tool. Kaplan-Meier curves were plotted for each tool and the log-rank test performed. The tools were compared using Cox-proportional hazard regression (CPHR). The tools were studied further in those without the following specified co-morbidities: Dementia, malignancy, Rockwood Frailty score of 6 or more, long-term oxygen therapy and previous do-not-resuscitate orders. Results: Of the 1,057 patients studied 146 (13.8%) died at hospital discharge and 284 were known to have died within 180 days. Overall survival proportion was 74.4% at 180 days and 8.6% of the population was censored before 180 days. Only the REDS and SOFA scores identified less than 50% of the population as high-risk. All tools, except the SIRS criteria, prognosticated for outcome at 180 days; Log-rank tests between high and low-risk groups were: REDS score p<0.0001, SOFA score p<0.0001, Red-flag criteria p=0.001, NICE high-risk criteria p=0.0001, NEWS2 score p=0.003 and SIRS criteria p=0.98. On CPHR, the REDS [Hazard ratio (HR) 2.54 (1.92-3.35)] and SOFA [HR 1.58 (1.24-2.03)] scores out-performed the other tools. In patients without the specified co-morbidities, only the REDS and SOFA scores risk-stratified for outcome at 180 days. Conclusion: In this study, all the risk-stratification tools studied were found to prognosticate for outcome at 180 days, except the SIRS criteria. The REDS and SOFA scores outperformed the other tools.